2009
DOI: 10.1038/ismej.2009.118
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage predation regulates microbial abundance and diversity in a full-scale bioreactor treating industrial wastewater

Abstract: Changes in the microbial community composition of a full-scale membrane bioreactor treating industrial wastewater were studied over a period of 462 days using a series of 16S rRNA gene clone libraries. Frequent changes in the relative abundance of specific taxonomic groups were observed, which could not be explained by changes in the reactor's conditions or wastewater composition. Phage activity was proposed to drive some of the observed changes. Bacterial hosts were isolated from a biomass sample obtained tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
159
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(168 citation statements)
references
References 52 publications
9
159
0
Order By: Relevance
“…A long-term study provides total bacterial and viral numbers for a given environment, allowing comparison of phage-host interactions (46). Although these methods indicate apparent population sizes, they cannot provide data for the abundance of a specific phage or its co-occurrence with a corresponding host strain.…”
Section: Resultsmentioning
confidence: 99%
“…A long-term study provides total bacterial and viral numbers for a given environment, allowing comparison of phage-host interactions (46). Although these methods indicate apparent population sizes, they cannot provide data for the abundance of a specific phage or its co-occurrence with a corresponding host strain.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, viruses that target beneficial bacteria (bacteriaphages) represent an unstudied and potentially rich research area. Metagenomic sampling reveals that phages are likely the most abundant and diverse ''organismal'' classes present in any microbial community and also possess the capability to regulate microbial abundance (Shapiro et al, 2010). The propagation and rapid evolution of phages is a persistent problem for the food industry, because the activation of a typically dormant phage can result in the complete loss of the Lactobacillus driven fermentation process (see Shimizu-Kadota et al, 1983).…”
Section: Microbial Symbioses and Disease Resistancementioning
confidence: 99%
“…Multiple studies have demonstrated parasite-mediated selection for host resistance both in the laboratory [1][2][3][4][5][6][7][8] and in natural populations [9][10][11][12]. Despite this propensity of hosts to evolve increased resistance, many natural populations are polymorphic with respect to resistance traits and disease remains ubiquitous.…”
Section: Introductionmentioning
confidence: 99%